2011
DOI: 10.1074/mcp.m111.007948
|View full text |Cite
|
Sign up to set email alerts
|

Sterile Protective Immunity to Malaria is Associated with a Panel of Novel P. falciparum Antigens

Abstract: The development of an effective malaria vaccine remains a global public health priority. Less than 0.5% of the Plasmodium falciparum genome has been assessed as potential vaccine targets and candidate vaccines have been based almost exclusively on single antigens. It is possible that the failure to develop a malaria vaccine despite decades of effort might be attributed to this historic focus. To advance malaria vaccine development, we have fabricated protein microarrays representing 23% of the entire P. falcip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
155
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 140 publications
(166 citation statements)
references
References 93 publications
9
155
0
Order By: Relevance
“…Each pad contains 824 peptide fragments expressed from Pf ORFs representing 702 unique proteins and three concentrations of 14 full-length proteins expressed using clinicalgrade manufacturing procedures. The protein targets on the array were selected from published studies done on a larger microarray containing 2,323 protein features after interrogating specimens from naturally exposed individuals (18), and specimens from sporozoite vaccine trials (19). The top 824 most immunoreactive antigens from these studies were printed on this down-selected array.…”
Section: Figmentioning
confidence: 99%
“…Each pad contains 824 peptide fragments expressed from Pf ORFs representing 702 unique proteins and three concentrations of 14 full-length proteins expressed using clinicalgrade manufacturing procedures. The protein targets on the array were selected from published studies done on a larger microarray containing 2,323 protein features after interrogating specimens from naturally exposed individuals (18), and specimens from sporozoite vaccine trials (19). The top 824 most immunoreactive antigens from these studies were printed on this down-selected array.…”
Section: Figmentioning
confidence: 99%
“…Using the ELISA assay, 20-31 donors displayed reactivity to CSP depending on the peptide used. Previous protein microarray serology results from our group showed that, although high levels of anti-PfCSP reactivity are seen in irradiated sporozoite-immunized volunteers, 34,50 antiPfCSP reactivity is much lower in naturally exposed individuals. 32 Reactivity to IVTT-produced P. falciparum CSP (PfCSP) and purified recombinant PfCSP was compared on the same chip; although good correlation was observed between the proteins, the magnitude of the response to the IVTT-produced PfCSP was five times lower than reactivity to the purified PfCSP.…”
Section: Discussionmentioning
confidence: 66%
“…Finally, it is also possible that both the type and the specificity of antibodies elicited by the two strains of mice in response to malaria infection contribute to the differential levels of protection observed. Studies in human malaria have shown that acquisition of antibodies against non-CSP antigens such as TRAP and LSA1 as well as against other less extensively characterized antigens is associated with the level of protection against malaria (52)(53)(54). Thus, it will be important to identify which antigens are recognized by the antibodies that result from Pyfabb/f Ϫ immunization of the different mouse strains as well as to characterize whether differences in their functional activities correlated with protection.…”
Section: Discussionmentioning
confidence: 99%